ENERGY AWARE SECURITY ALGORITHM DECISION METHOD FOR INTERNET OF THINGS USING SSL/TLS FOR WIRELESS NETWORK - Cho, Tae-Ho (International Journal of Research -GRANTHAALAYAH, 2015)
The Internet of Things (IoT) is an ever evolving infrastructure of physical objects and Internet-enabled devices and systems featuring IP addresses for connectivity. Physical objects consist of home appliances, electronic gadgets, machinery, healthcare items, wearable devices and anything that could be connected to the Internet. Each type of connection requires particular types of security service. Security algorithms in user devices are fixed by default and selected based on preferences. This limitation causes energy waste since a user might be using all services in an algorithm, even those the user does not need. In order to counter this problem, we propose an energy aware security service selection method that saves energy by selecting only particular types of security service required by a given connection. In this paper, we compared the energy consumption of each communication to provide integrity, authentication, and confidentiality in Secure Sockets Layer/Transport Layer Security (SSL/TLS) with our proposed method. The experimental results demonstrate the validity of our proposed method. Our proposed method saved 54.94% energy for integrity and 74.52% for authentication.